TEACHER EFFECTIVENESS: WHAT DO STUDENTS AND INSTRUCTORS SAY? - Carver, Lin B; Rapp, Lisa (Advances in Social Sciences Research Journal, 2018)
Educators often discuss teaching strategies as the means to enhance students’ education; however, many effective educators share characteristics that also strongly influence students’ learning. Few studies have made progress in identifying the characteristics of effective teachers. This study used data from an online survey completed by 733 graduate or undergraduate university students and 92 full time university instructors to explore their perceptions about the characteristics of effective university instructors. Instructors, undergraduate and graduate students from a Catholic, Liberal Arts University participate in an online survey. The survey was used to explore the characteristics of effective instructors who taught online and on-ground college courses. Using a Likert scale rating and a rank ordering of importance of 19 characteristics which were combined to inform 10 categories, participants rated how important the viewed behaviors/characteristics in an effective instructor for online and on-ground coursework. Results indicated important similarities and differences in perceptions between instructors and students. Both students and instructors rated knowledgeable as the most important characteristic in online and on-ground instruction. The only characteristic that differed depending on the age of the participant was humor. The younger the participant, the more important humor in instruction was.